Hubungan Frekuensi Konsumsi Pangan, Keanekaragaman Konsumsi Pangan dan Tingkat Stres dengan Hipertensi pada Lanjut Usia (Lansia) - Kusumawati, Astiwi Fadillah; Abdullah, Abdullah; Khairani, Masayu Dian; Akhriani, Mayesti (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2024)
Background: Hypertension is a serious medical condition and can increase the risk of other diseases. This disease causes premature death worldwide, with >1 in 4 men and 1 in 5 women suffering from this disease. The purpose of this study was to determine the relationship between the frequency of food consumption, diversity of food consumption and stress levels in the elderly in Pekon Sumber Agung, Ambarawa District, Pringsewu Regency. Sampling used purposive sampling. The population in this study were the elderly in Pekon Sumber Agung, Ambarawa District, Pringsewu Regency. The number of samples was 55 elderly people. Data were collected by direct interviews with respondents and analyzed bivariately using the Gamma test Method: This study is a quantitative study with a cross-sectional research design. Results: The results of this study indicate that there is a relationship between the frequency of food consumption (p-0.005), diversity of food consumption (p-0.001), and stress levels (p-0.001) with hypertension in the elderly in Pekon Sumber Agung, Ambarawa District, Pringsewu Regency. Conclusion: hypertension in the elderly is caused by the frequency of food consumption, the diversity of food consumption that is not diverse enough and stress levels. Suggestions for Pekon Sumber Agung, Ambarawa District, Pringswu Regency with the results of this study, the researcher hopes that routine posyandu will be carried out in every hamlet and more activities will be added at the elderly posyandu such as elderly gymnastics and nutritional counseling